Time is on my side: Steganography in filesystem metadata. (7th August 2016) - Neuner, Sebastian; Voyiatzis, Artemios G.; Schmiedecker, Martin; Brunthaler, Stefan; Katzenbeisser, Stefan; Weippl, Edgar R.
Abstract: We propose and explore the applicability of file timestamps as a steganographic channel. We identify an information gap between storage and usage of timestamps in modern operating systems that use high-precision timers. Building on this, we describe a layered design of a steganographic system that offers stealthiness, robustness, and wide applicability. The proposed design is evaluated through theoretical, evidence-based, and experimental analysis for the case of NTFS using datasets comprising millions of files. We report a proof-of-concept implementation and confirm that the embedded information is indistinguishable from that of a normal filesystem use. Finally, we discuss the digital forensics analysis implications of this new information-hiding technique.